On some properties of Abian's semiring and its zero divisor graphs - Sarifa Khatun; Jayasri Sircar; Sk. Md. Abu Nayeem (IndoMS, 2020)
In this paper, we have studied some properties of Abian's semiring, especially about the supremum of a subset of an Abian's semiring. We have also considered the zero divisor graphs of Abian's semiring and found some properties of those graphs.